Large displacement analysis of dry-joint masonry arches subject to inclined support movements - Ferrero, Chiara; Calderini, Chiara; Portioli, Francesco; Roca, Pere (Engineering structures, 2021)
•The response of masonry arches to large support displacements is analysed.•Two numerical approaches, finite element and rigid block modelling, are adopted.•Numerical analyses are performed varying the direction of support displacements.•New conclusions on the effect of inclined displacements are drawn.•The sensitivity of the results to the number of voussoirs is investigated. In this paper, the structural response of a segmental dry-joint masonry arch subjected to increasing support displacements was investigated. The arch behaviour was analysed in the framework of large displacements using finite element (FE) and rigid block (RB) models, both based on a micro-modelling strategy. Once the two modelling approaches were validated against experimental results from literature, nonlinear analyses were carried out considering different configurations of support displacements (i.e. vertical, horizontal and inclined). The effect of the displacement direction on the arch response was evaluated in terms of initial hinge position, collapse mechanism, support reaction-displacements curves as well as ultimate displacement capacity. The sensitivity of the results to the number of voussoirs was also investigated. The good agreement between the results from the two models allowed to draw new conclusions about the response of segmental masonry arches to inclined support displacements in the large displacement regime. A limit displacement domain computed as a function of the direction of the support displacements is also proposed.